Expression of p-AMPK in colorectal cancer revealed substantial diverse survival patterns - Khabaz, Mohamad Nidal (Pak J Med Sci, 2019)
OBJECTIVE: Several cancers have showed differences in the role of p- AMPK in cancer growth, progression and prognosis, and little is identified regarding the significance of p-AMPK expression in colorectal adenocarcinoma. Therefore, this report will define p-AMPK phenotype in a panel of colorectal carcinomas and explore the relationship between this phenotype and tumor clinicopathological features. METHODS: A total of 228 cases comprising 155 large intestine cancers and 73 controls (40 benign tumors and thirty three non-cancerous tissues) were employed in tissue microarray construction. Immunohistochemistry (IHC) staining was applied to reveal p-AMPK expression. This study was carried out in the pathology lab of King Abdulaziz University Hospital over a duration of 15 months and was completed on 7(th) July 2018. RESULTS: Phosphorylated AMPK was identified in 133 (85.8%) of colorectal cancers and 73 (100%) control cases. Histologic type was noticeably correlated with p-AMPK immunostaining (P= 0.001), high score of p-AMPK immunostaining is more frequent in control cases. Considerable varied survival models were observed with neoplasm size, metastatic tumor, recurrence and disease relapse (P-values<0.01). Survival estimates are considerably healthier in positive cases which have one of the following features size less than 5 cm, absence of metastatic tumor, no reoccurrence or disease relapse. CONCLUSIONS: The present study showed a reduction in the IHC staining of p-AMPK in colorectal cancer compared with controls. IHC staining of p-AMPK can be a supportive marker in predicting prognosis and survival estimates of colorectal tumors with specific clinical factors.